JUMLAH LIMFOSIT DAN NEUTROFIL DIHUBUNGKAN DENGAN SERVICE PER CONSEPTION (S/C), CALVING INTERVAL (CI) DAN ESTRUS POST PARTUM (EPP) PADA SAPI POTONG DI YOGYAKARTA - , AZKA NOVITA PUTRI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Peripheral blood examination is one of the important laboratory procedures in order to establish the diagnosis of various disease. One of the most important and routinely examined blood elements is the lymphocyte and neutrophyl count. Abnormality in their quantitative may lead to the understanding of bodyâs rensponse mechanism to foreign body (Sukorini et al., 2007). Reproductive performance includes Estrus Post Partus (EPP), calving interval (CI), service per conception (S/C) and (days open/DO) (Nuryadi, 2011). This research used 23 beef cattle blood sample in Seyegan and Nanggulan, Yogyakarta (10 Ongole-Cross Breed Cattle and 13 Simmental-Cross Breed Cattle blood sample). Blood sampling using a disposable syringe 5 ml of each cattle samples in the data, 3 ml blood from coccigea venous was put into EDTA Vacutainer tubes and stored in a cool box and were delivered to The Integrated Research and Examination Laboratory of Gadjah Mada University (LPPT UGM) for measurement of the neutrophil and lymphocyte count. The result of lymphocyte and neutrophylâs count in the group of cattle with S/C 1,0 â 2,0 were not significantly different than group of cattle with S/C >2,0. The group of cattle with EPP 30-60 days were significantly higher (P<0,05) than the group of cattle with RPP > 60 days. The group of cattle with CI 12-14 months were significantly higher (P<0,05) than the group of cattle with CI > 14 months. Lymphocyte and neutrophylâs count have no direct effect against S/C , EPP and CI because still in normal range of cattle bloodâs count internationally, so that lymphocyte and neutrophylâs count have no effect to quality of S/C, EPP and CI in cattle.